1983
DOI: 10.1111/j.1365-2125.1983.tb02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture on ampicillin pharmacokinetics, glomerular filtration rate and renal plasma flow in resting subjects.

Abstract: 1 Differences in drug kinetics between supine rest and ambulation have been reported, but the relative contribution of postural changes and changes in the level of physical activity has not been evaluated. 2 Ampicillin pharmacokinetics, glomerular filtration rate (GFR) and renal plasma flow (RPF) were studied in six male volunteers at rest in the sitting and lying position with an interval of 1 week. 3 After intravenous administration ampicillin kinetics, analyzed according to a two-compartment open model, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several studies failed to show any relevant postural effect on metabolism or elimination of the drugs administered intravenously [44][45][46][47]. As there is no absorption phase after intravenous application, the effects of posture on gastric emptying are not relevant.…”
Section: Posture and Route Of Administrationmentioning
confidence: 99%
“…Several studies failed to show any relevant postural effect on metabolism or elimination of the drugs administered intravenously [44][45][46][47]. As there is no absorption phase after intravenous application, the effects of posture on gastric emptying are not relevant.…”
Section: Posture and Route Of Administrationmentioning
confidence: 99%
“…Since no significant differences in the key pharmacokinetic parameters were observed for the 2 treatments administered during the day, it is reasonable to conclude that posture did not have a significant effect on the rate of absorption of cefprozil, volume of distribution and AUC of this cephalosporin. Unlike cefprozil, the effect of sitting vs standing posture on the volume of distribution of ampicillin has been reported (Breiby et al 1983). …”
Section: Discussionmentioning
confidence: 98%
“…These phenomena are caused by changes in absorption (Adir & Barr 1977;Davenport 1966), distribution (Breiby et al 1983), metabolism (DiSanto & Wagner 1972;Jori et al 1973;Patel et al 1977;Radzialowski & Bousquet 1968;Roberts & Turnbull et al 1970), and elimination (Beckett & Rowland 1964;Koike et al 1984;Roberts & Denton 1980). Several antibacterial drugs such as amoxicillin (Roberts & Denton 1980), ampicillin (Breiby et al 1983), tetracycline (Adir & Barr 1977) and cinoxacin (Koike et al 1984) have demonstrated pharmacokinetic changes due to time of administration or posture.…”
mentioning
confidence: 96%
“…The primary weaknesses of OAT are inter-individual variability in the clinical outcomes and AMR owing to inter-individual variability in pharmacokinetics [25,29,30,[96][97][98] and hepatobiliary vs. renal clearance [20] delaying the achievement of the minimum inhibitory concentration (MIC) in urine [23,87]. The oral bioavailability of OAT differs with race [32,99], food intake [97], inter-individual variability in the gastric emptying time [100], posture (supine or ambulatory) [101,102], and the general health status of the patient [103]. MIC is the lowest antimicrobial concentration required to prevent the visible growth of the test strain of a microbe after a definite incubation period under strictly controlled in vitro conditions [104].…”
Section: Swots Of Oral Antimicrobial Therapy (Oat) For Cystitismentioning
confidence: 99%
“…Opportunities-predictable oral bioavailability [30,101,102,109] could reduce the delay in achieving urinary MIC [28,105], and informed clinical practices [110,111] could counter the emergence of AMR.…”
Section: Volume Of Distribution (Vd) and Clearance Of Oatmentioning
confidence: 99%